Performance and optimization of spray drying technique on the production of microparticles of Haruan, Channa striatus extract - Lee, Yun Hui (2015)
Channa striatus, the fish a carnivorous, air breathing freshwater species can be found throughout Malaysia including Sabah and Sarawak. It is well known as one of the famous ethno-pharmacology for wound healing and being consumed almost everywhere in the community of Malaysia. Thus, this research is an innovative work to carry out the transformation of Channa striatus to microparticles using spray drying technique. To carry out the research, it was firstly, fresh Channa striatus supplied by local farmer undergone an overnight hypothermic stress treatment with temperature below -20oC and filleted prior to cook in pressure cooker for an hour with distilled water. The extract was cooled to room temperature, before filtration using vacuum pump for purification. Filtered Channa striatus extract was encapsulated with three different types of binders which were carboxymethylcellulose (CMC), maltodextrin and xanthan gum in fixed concentration and spray dried distinctively to produce microparticles. The spray drying process were conducted by altering the process parameters which were drying temperature, air flow rate, pump flow rate and binder concentration for the purpose of optimization in order to produce microparticles that are high in the content of protein and antioxidant with minimum size and moisture content. The Channa striatus microparticles then were used for physico-chemical analysis namely particle size distribution, moisture content, protein content using Kjeldahl method and antioxidant activity using DPPH radical scavenging method. The results obtained from two-level factorial designs shows that, the optimum spray drying process to produce Channa striatus microparticles in the sequence of drying temperature, pump flow rate and air flow rate are; CMC binder was 130oC, 151.04 ml/hr, 55.13 m3/hr, 0.7% w/v binder produced microparticles with the size of 4.4μm, moisture content of 5.1%, antioxidant activity of 54.55% and protein content of 49.07% ; maltodextrin binder was 130oC, 150.30 ml/hr, 55.00 m3/hr, 0.7% w/v binder which produce microparticles with the size of 11.5μm, moisture content of 4.1%, antioxidant activity of 46.22% and protein content of 46.49% and xanthan gum binder was 150oC, 150 ml/hr, 59.51 m3/hr, 0.5% w/v binder which produce microparticles with the size of 2.98μm, moisture content of 7.9%, antioxidant activity of 53.32% and protein content of 53.52%. The size of the microparticles obtained are in the scale of micron size, there is potential in producing Channa striatus particles in nanosize by refining the spray drying process in the aspects of spray drying parameters. Furthermore, the percentage of protein and antioxidant that was observed in the microparticles proven that Channa striatus microparticles produced with spray drying technique have a good prospective to be marketed as supplement or drugs for wound healing remedy.